Bureaucratic Politicization in the Process of Changing Bureaucratic Positions After the Vacancy of the Deputy Regent of Dharmasraya Regency in 2022 - Alika, Yulvia; Valentina, Tengku Rika; Hendrik, Doni (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Bureaucratic politicization refers to introducing bureaucratic reform in the management of regional government. The regional head and deputy regional head posts are political roles that oversee administrative positions within a region, so political influence is inherently intertwined with the bureaucracy. Dharmasraya Regency exhibits signs of bureaucratic politics, as seen by a vacancy in the position of deputy regent. This vacancy has resulted in numerous examples of non-job ASN inside the government of Dharmasraya Regency. This thesis seeks to analyze the political dynamics involved in the transition of bureaucratic positions in Dharmasraya Regency, particularly after the vacancy of the deputy regent position. This study employs a qualitative research methodology utilizing a case study approach. This thesis uses the theory of bureaucratic politicization pioneered by Barbara Geddes. The findings of this study suggest that there are indicators of the techniques employed by the regent in his role as PPK to determine bureaucratic positions. The regent also has a vested interest in the bureaucracy, as he desires a loyal and efficient bureaucratic system to ensure continued control until the end of his term. The regent's politicization of the bureaucracy is seen in the ambiguous enforcement of heavy sanctions against ASN.